Extreme weather, school logbooks and social vulnerability: The Outer Hebrides, Scotland, in the late nineteenth and early twentieth centuries. (October 2022) - Naylor, Simon; Macdonald, Neil; Bowen, James P.; Endfield, Georgina
Abstract: This paper demonstrates the value of school logbooks, an unusual and hitherto underused archival source, to the field of the historical geographies of weather and climate. It examines logbooks for schools across the Outer Hebrides, or Western Isles, off the west coast of mainland Scotland, ranging from the late nineteenth century until the early twentieth century. The weather had numerous and varied impacts on everyday life on the islands and was frequently recorded in school logbooks. The paper shows that islanders were especially vulnerable to extreme weather events – typically strong winds, heavy rain, storms and snow – which affected children's school attendance, health and well-being. It is argued that vulnerability to extreme weather reflected the wider social vulnerability of the islands' crofting communities. Highlights: School logs are valuable archival sources for weather and climate history studies. Scottish Islanders lived in 'weather worlds' and were vulnerable to extreme weather. Islanders' vulnerability to extreme weather was due to a wider social vulnerability.